Assessing changes in the study of religious communities in digital religion studies - Campbell, Heidi (Church, Communication and Culture, 2016)
This article provides a focused review of researches undertaken within Digital religion studies in the last three decades, specifically highlighting how religious communities have been studied and approached within this area. It highlights the dominant theoretical and methodological approaches employed by scholars during what is being described as the four stages of research on religious communities emerging over this period of time. Thus, this article presents the findings of key studies emerging during these stages to illuminate how the study of religious communities online has evolved over time. It also offers insights into how this evolution specifically relates to the study of Catholic community online. Finally, a theoretical analysis is given, assessing current research on religious communities within Digital Religion studies, and approaches for future research are proposed.